Entre manas e manos : uma etnografia com o movimento de mulheres do hip hop e a casa do hip hop Sanca - Araujo, Ayni Estevão de (Universidade Federal de São Carlos, 2016)
In this study, hip hop is shown as a culture in permanent movement. The objective of the study is to identify constitutional factors of the hip hop culture. The study design includes field work focusing on female hip hoppers from São Paulo and São Carlos House of Hip Hop institution. Activities from these two groups were observed and the dynamics of the working functionality of the groups were described. There were also descriptions of interactions between different mobilization forms and their influences, performed by the active characters involved in this process. It was observed that the political awareness between the study groups is shaped throughout the characteristics of the speech of the hip hoppers and their practical actions. Therefore, this study concludes that there were two distinct mobilization manners on the way the two groups experience hip hop culture. However, this process is constantly renovated by the interactions and simultaneous affect from between the groups.
Keywords: Hip hop; Gênero; Raça; Política; Gender; Race; Politics; CIENCIAS HUMANAS::ANTROPOLOGIA